2021
DOI: 10.3389/fonc.2021.738252
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Effects on Tumor: Pathway and Mechanism

Abstract: Chronic stress is an emotional experience that occurs when people encounter something they cannot adapt to. Repeated chronic stress increases the risk of a variety of diseases, such as cardiovascular disease, depression, endocrine disease, inflammation and cancer. A growing body of research has shown that there is a link between chronic stress and tumor occurrence in both animal studies and clinical studies. Chronic stress activates the neuroendocrine system (hypothalamic-pituitary-adrenal axis) and sympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 115 publications
0
28
0
Order By: Relevance
“…However, other studies have shown that patients with high dopamine receptor 1 (DRD1) expression have a worse prognosis, while dopamine and its receptor can promote tumor progression by PI3K/AKT signaling pathway activation (Yan et al, 2020). In addition, an increasing number of studies have focused on exploring interactions between adrenergic receptors and HCC progression (Wu et al, 2016;Hong et al, 2021). A study by Liu et al (2021) showed that environmental stress could induce anti-tumor immunity and could sensitize immunotherapy against HCC by modulating β-adrenergic receptors/CCL2 axis.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that patients with high dopamine receptor 1 (DRD1) expression have a worse prognosis, while dopamine and its receptor can promote tumor progression by PI3K/AKT signaling pathway activation (Yan et al, 2020). In addition, an increasing number of studies have focused on exploring interactions between adrenergic receptors and HCC progression (Wu et al, 2016;Hong et al, 2021). A study by Liu et al (2021) showed that environmental stress could induce anti-tumor immunity and could sensitize immunotherapy against HCC by modulating β-adrenergic receptors/CCL2 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress refers to the nonspecific pathophysiological response caused by the change of the body's steady state under the long-term stimulation of various adverse factors in vivo and abroad. Generally speaking, it is the emotional experience of people under the pressure that they are difficult to adapt [ 7 , 8 ]. The source of this stress is often psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-apoptotic factor AKT can inhibit Bcl-2-associated death protein (BAD) and lead to the dissociation of Bcl-2 from the mitochondrial membrane, thereby inhibiting apoptosis [ 47 ]. Radiation resistance is a common phenomenon in NPC cells and is mainly related to autophagy [ 48 ]. The process of autophagy is broken down into four critical steps: initiation, nucleation, maturation, and degradation [ 49 ].…”
Section: Introductionmentioning
confidence: 99%